Structure Collapse and Abandonment: Patterns in the Archaeological Record - Socha, Amy N. (Tufts Archival Research Center, 2021)
Abandonment is the process by which a structure is transformed from systemic context – when it is occupied - to archaeological context. It is both a single event or moment in time when a structure’s context changes and all of the conditions and events preceding and following that moment. Abandonments can be categorized by why they occur and how long a structure remains abandoned. Causes of structure abandonment are varied, including natural disaster, warfare, change in the structure’s purpose, and challenges to social hierarchy. Only rarely is an abandonment caused by only one thing, it is more often a combination of multiple factors. When a structure is permanently abandoned, it is acted upon primarily by nature rather than people, and its collapse is dictated by the force of gravity and rates of weathering. These forces act on the structure as a whole and can be quantified based on principles of physics and geology. In comparing a stone structure to a natural cliff, I am able to apply the concept of hillslope diffusion to the formation of mounds from an abandoned structure. By applying this concept I propose to calculate the length of time since a structure was abandoned using a quadratic equation representative of the shape of the mound. Utilizing this method could provide an upper limit for the occupation of a site that could be calculated during survey prior to excavation, providing information on settlement patterns and regional abandonments, as well as informing future excavations to answer the classic question: where should I dig?